Are they using my feedback? The extent of students' feedback use has a large impact on subsequent academic performance. Issue 4 (19th May 2017) - Zimbardi, Kirsten; Colthorpe, Kay; Dekker, Andrew; Engstrom, Craig; Bugarcic, Andrea; Worthy, Peter; Victor, Ruban; Chunduri, Prasad; Lluka, Lesley; Long, Phil
Abstract : Feedback is known to have a large influence on student learning gains, and the emergence of online tools has greatly enhanced the opportunity for delivering timely, expressive, digital feedback and for investigating its learning impacts. However, to date there have been no large quantitative investigations of the feedback provided by large teams of markers, feedback use by large cohorts of students, nor its impact on students' academic performance across successive assessment tasks. We have developed an innovative online system to collect large-scale data on digital feedback provision and use. Our markers ( n  = 38) used both audio and typed feedback modalities extensively, providing 388 ± 4 and 1126 ± 37 words per report for first- and second-year students, respectively. Furthermore, 92% of first year and 85% of second-year students accessed their feedback, with 58% accessing their feedback for over an hour. Lastly, the amount of time students spent interacting with feedback is significantly related to the rate of improvement in subsequent assessment tasks. This study challenges assertions that many students do not collect, or use, their feedback. More importantly, we offer novel insights into the relationships between feedback provision, feedback use and successful academic outcomes.